2017
DOI: 10.15761/brcp.1000135
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms of angiogenic factors in skin and wound tissue in per2-mutant mice

Abstract: It has recently been reported that circadian gene Period 2 (per2) regulates mRNA expression of vascular endothelial growth factor gene (Vegf) in some tumor cells. It still remains unknown, however, whether per2 has an effect on expression of angiogenic factors during the wound healing process. To investigate the circadian rhythms of angiogenic factors in intact skin and wound tissue in per2-mutant and control mice, we used a skin incision wound model on per2-mutant and control mice, and analyzed circadian rhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…There was no statistically significant difference between mutant and control mice in the percentages of the vascular areas in the wound tissues 7 through 35 days after the skin incision. We have previously shown the difference in circadian rhythms of angiogenic factors in the skin and wound tissues in per2 mutant B6.Cg-Per2tm1Brd Tyrc-Brd/J mice compared with control B6(Cg)-Tyrc-2J/J mice [3]. Therefore, we hypothesized that the mutant mice would show a difference in the recovery of vasculature from the skin injury.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…There was no statistically significant difference between mutant and control mice in the percentages of the vascular areas in the wound tissues 7 through 35 days after the skin incision. We have previously shown the difference in circadian rhythms of angiogenic factors in the skin and wound tissues in per2 mutant B6.Cg-Per2tm1Brd Tyrc-Brd/J mice compared with control B6(Cg)-Tyrc-2J/J mice [3]. Therefore, we hypothesized that the mutant mice would show a difference in the recovery of vasculature from the skin injury.…”
Section: Resultsmentioning
confidence: 93%
“…NONO is a binding partner of a circadian period protein Per2, and the NONO-PER protein complex was shown to couple the clock and the cell cycle by activating the rhythmic transcription of the cell cycle checkpoint gene Ink4a [2]. We have previously shown the difference in circadian rhythms of angiogenic factors in the skin and wound tissues in per2 mutant B6.Cg-Per2tm1Brd Tyrc-Brd/J mice compared with control B6(Cg)-Tyrc-2J/J mice [3].…”
Section: Introductionmentioning
confidence: 96%
“…TaqMan Gene Expression Assays (Thermofisher, Waltham, MA, USA) were used to assay Tek (Tie2) (Mm004432343_m1), Angpt1 (Mm00456503_m1), Angpt2 (Mm00545822_m1) [ 17 ], ActB (Mm02619580_g1), AP3D1 (Mm00475961_m1), and GusB (Mm01197698_m1). qPCR products were generated using the QuantStudio TM 5 system with TaqMan Fast Advanced Master Mix (Applied Biosystems, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether the changes in pTie2/Tie2 ratio may be due to changes in the Tie2 regulatory protein VE-PTP 17 , ELISA was performed to determine VE-PTP protein concentration. No significant differences in VE-PTP protein concentrations were seen between young mdx/utrn +/− mice (2095.981 ± 625.203 pg/mL) compared to young WT mice (1888.470 ± 719.714 pg/mL) (p = 0.8486) (Figure 3E).…”
Section: Ptie2/tie2mentioning
confidence: 99%
“…Importantly, several studies have identified RORs and Rev-ErbAs as regulators of circadian rhythm, lipid homeostasis, and angiogenesis [122,134]. Others suggest that an interconnected relationship may exist between these functions and systemic and ocular-related vascular diseases [128,[135][136][137][138][139]. In a rat model of diabetic mellitus type 2, Busik et al discovered DR to be a downstream consequence to bone marrow neuropathy succeeded by decreases in endothelial progenitor cell (EPC) number, migratory potential, and reparative capacity.…”
Section: Retinoic Acid Receptor (Rors) and Rev-erbsmentioning
confidence: 99%